CONCEPT WORK ENGAGEMENT IN INDONESIAN STARTUPS - Cahyadi, Herman; Maupa, Haris; Handoyo, Sarwo Edy (Graduate Program of Universitas Tarumanagara, 2024)
he development of information technology is a good condition for the growth of startups in Indonesia. Nevertheless, the growing number of startups is followed by many other challenges, especially those related to human resource management. Startups are a different business model than ordinary companies. Startups have a high dynamic due to the demand always to be innovative. This is a challenge in managing human resources within the startup. This research aims to build the concept of work engagement in Indonesian startups.